Metacognitive Scaffolding in Reading Comprehension: Classroom Observations Reveal Strategies to Overcome Reading Obstacles of Engineering Students at QUEST, Nawabshah, Sindh, Pakistan - Mansoor Ahmed, Channa; Zaimmuariffudin Shukri, Nordin; Abdul Malik, Abassi (Canadian Center of Science and Education, 2018)
This study aimed at investigating the development of reading comprehension of engineering students through metacognitive strategies and scaffolding. This study used 12 classroom observations in four engineering departments of one public university in Pakistan. The researcher observed 3 classes in each department at the time of read-aloud sessions. The class in each department was comprised on minimum 55 students and maximum 75 students. The researcher himself conducted all the 12 observations to maintain reliability without interfere of the complete teaching method. Teacher in each class was introduced by the observer and his aim to come in the first observation session. The observer sat at the back of every classroom and noted all instructional practices carefully on the field-notes based on teachers using metacognitive strategies to support students in terms of reading comprehension instructions. This study revealed the promising results based on metacognitive scaffolding and strategies as the most important tools for engineering students and language teachers to use for the development of reading and comprehension.